2013
DOI: 10.1016/j.jmoldx.2012.07.005
|View full text |Cite
|
Sign up to set email alerts
|

APC Germline Mutations in Individuals Being Evaluated for Familial Adenomatous Polyposis

Abstract: Inactivating APC mutations cause familial adenomatous polyposis, classically characterized by hundreds to thousands of adenomatous colorectal polyps and cancer. Historically, 98% of pathogenic alterations in APC are nonsense or frameshift mutations; however, few reported series have used techniques that test for large deletions or duplications. Splice site mutations are only rarely documented. Consecutive cases (n = 1591) submitted for complete APC gene analysis during a 4-year period were reviewed. Testing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 86 publications
(22 reference statements)
1
34
0
2
Order By: Relevance
“…and splice site changes [129]. It was observed that FAP patients show increased risk for the ACC formation, compared with the general population.…”
Section: Prace Poglądowementioning
confidence: 97%
See 3 more Smart Citations
“…and splice site changes [129]. It was observed that FAP patients show increased risk for the ACC formation, compared with the general population.…”
Section: Prace Poglądowementioning
confidence: 97%
“…In its typical form, FAP manifests as hundreds to thousands of colorectal adenomatous polyps and cancer [129], while Gardner syndrome reveals gastrointestinal polyposis and other lesions, such as osteomas, epidermoid cysts, hepatoblastoma, papillary or follicular thyroid cancer, and adrenal adenomas [130]. The molecular cause underlying these syndromes is found at the locus 5q22.2, containing the adenomatous polyposis coli (APC) gene, which acts as a tumour suppressor by decreasing the activity of b-catenin.…”
Section: Familial Adenomatous Polyposismentioning
confidence: 99%
See 2 more Smart Citations
“…The gene encodes a protein that negatively regulates the β-catenin oncoprotein. In the absence of the APC gene, the β-catenin protein interacts with various transcription factors as it accumulates in the nucleus to upregulate genes that propagate the cell cycle progression [ 28 ]. Germline mutations include deletions, insertions, nonsense, and missense mutations.…”
Section: Geneticsmentioning
confidence: 99%